A study on the impact and buffer path of the internet use gap on population health: Latent category analysis and mediating effect analysis - He, Yuanyuan; Zhou, Lulin; Xu, Xinglong; Li, JunShan; Li, Jiaxing (Frontiers in Public Health, 2022)
Background: The development of Internet information technology will generate an Internet use gap, which will have certain adverse effects on mental health, but Internet information dependence can alleviate these negative effects. Objective: This article is to demonstrate the negative impact of the Internet use gap on mental health in developing countries and to propose improvement paths. Methods: This article used the 2018 China Family Tracking Survey database (N = 11086), Latent Class Analysis (LCA), Ordinary Least Squares regression model (OLS), Bootstrap intermediary effect test, Propensity Score Matching (PSM) test, and other methods. Results: (1) The Internet users can be divided into light-life users (N = 1061, 9.57%), all-around users (N = 1980, 17.86%), functional users (N = 1239, 11.18%), and pure-life users (N = 6806, 61.39%). (2) There are differences in the results of the Internet's effect on mental health caused by the Internet use gap. When the light-life users were taken as the reference group, the effect coefficients of all-around users, functional users, and pure-life users on mental health were 0.376 (P<0.05), -0.729 (P<0.01), and -1.245 (P<0.01), respectively. Internet information dependence can promote the development of mental health, and the effect coefficient is 0.070 (P<0.05). (3) The Internet use gap can affect mental health through the indirect path of Internet information dependence, and some of the IEs are significant. When the light life user group was taken as the reference group, the mediating effect values of all-round users and functional users on mental health were 0.091 and 0.085 through Internet information dependence, and the 95% Bootstrap confidence intervals were [0.062, 0.124] and [0.055 0.119], and the corresponding mediating effects accounted for 16.70% and 13.70%, respectively. Conclusion: The Internet use gap has a significant effect on mental health, and Internet information dependence plays an intermediary role in this effect path. The study proposes that attention should be paid to the diversified development of Internet use, the positive guiding function of Internet information channels should be made good use of, and the countermeasures and suggestions of marginalized groups in the digital age should also be paid attention to and protected.